New Techniques for SIDH-based NIKE - Urbanik David; Jao David (Journal of Mathematical Cryptology, 2020)
We consider the problem of producing an efficient, practical, quantum-resistant non-interactive key exchange (NIKE) protocol based on Supersingular Isogeny Diffie-Hellman (SIDH). An attack of Galbraith, Petit, Shani and Ti rules out the use of naïve forms of the SIDH construction for this application, as they showed that an adversary can recover private key information when supplying an honest party with malformed public keys. Subsequently, Azarderakhsh, Jao and Leonardi presented a method for overcoming this attack using multiple instances of the SIDH protocol, but which increases the costs associated with performing a key exchange by factors of up to several thousand at typical security levels. In this paper, we present two new techniques to reduce the cost of SIDH-based NIKE, with various possible tradeoffs between key size and computational cost.